Zoster Vaccine and the Risk of Postherpetic Neuralgia in Patients Who Developed Herpes Zoster Despite Having Received the Zoster Vaccine. (1st June 2015) - Tseng, Hung Fu; Lewin, Bruno; Hales, Craig M.; Sy, Lina S.; Harpaz, Rafael; Bialek, Stephanie; Luo, Yi; Jacobsen, Steven J.; Reddy, Kavya; Huang, Po-yin; Zhang, Jeff; Anand, Sean; et al.
Abstract: Background. Although it is evident that zoster vaccination reduces postherpetic neuralgia (PHN) risk by reducing herpes zoster (HZ) occurrence, it is less clear whether the vaccine protects against PHN among patients who develop HZ despite previous vaccination. Methods. This cohort study included immunocompetent patients with HZ. The vaccinated cohort included 1155 individuals who were vaccinated against HZ at age ≥60 years and had an HZ episode after vaccination. Vaccinated patients were matched 1:1 by sex and age with unvaccinated patients. Trained medical residents reviewed the full medical record to determine the presence of HZ-related pain at 1, 2, 3, and 6 months after HZ diagnosis. The incidence of PHN was compared between vaccinated and unvaccinated –patients. Results. Thirty vaccinated women (4.2%) experienced PHN, compared with 75 unvaccinated women (10.4%), with an adjusted relative risk of 0.41 (95% confidence interval, .26–.64). PHN occurred in 26 vaccinated men (6.0%) versus 25 unvaccinated men (5.8%), with an adjusted relative risk of 1.06 (.58–1.94). These associations did not differ significantly by age. Conclusions. Among persons experiencing HZ, prior HZ vaccination is associated with a lower risk of PHN in women but not in men. This sex-related difference may reflect differences in healthcare-seeking patterns and deserve further investigation.